A scoping review of home-produced heroin and amphetamine-type stimulant substitutes: implications for prevention, treatment, and policy. Issue 1 (December 2016) - Hearne, Evelyn; Grund, Jean-Paul; Van Hout, Marie; McVeigh, Jim
Abstract Several home-produced substances such askrokodil andboltushka are prevalent in many Eastern European countries. Anecdotal reports of its use have been circulating in Germany and Norway; however, this has not been confirmed. Its use has also been reported by the media in the USA, although only one confirmed report of its use exists. Home-produced drugs are associated with high levels of morbidity and a number of complex health issues such as the spread ofblood borne viruses, gangrene, andinternal organ damage . The high incidence of HIV rates amongst people who inject home-produced substances is a public health concern. The resulting physical health consequences of injecting these crude substances are very severe in comparison to heroin or amphetamine acquired in black markets. Due to this fact and the increased mortality associated with these substances, professionals in the area of prevention, treatment, and policy development need to be cognisant of the presentation, harms, and the dangers associated with home-produced substances globally. This scoping review aimed to examine existing literature on the subject of home-produced heroin and amphetamine-type stimulant substitutes. The review discussed the many implications such research may have in the areas of policy and practice. Data were gathered through the use of qualitative secondary resources such as journal articles, reports, reviews, case studies, and media reports. The home production of these substances relies on the utilisation of precursor drugs such as less potent stimulants, tranquillizers, analgesics, and sedatives or natural plant ingredients. The Internet underpins the facilitation of this practice as recipes, and diverted pharmaceutical sales are available widely online, and currently, ease of access to the Internet is evident worldwide. This review highlights the necessity of prevention, education, and also harm reduction related to home-produced drugs and also recommends consistent monitoring of online drug fora, online drug marketplaces, and unregulated pharmacies.